Kedudukan Surat Keterangan Pembebasan Lahan Oleh Pemangku Adat Terhadap Pemilikan Tanah Di Atas Tanah Ulayat Di Desa Pantai Cermin Kecamatan Tapung Kabupaten Kampar - Irwani, Nike; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Ulayat land is communal property which may not and cannot be registered in the name of one orseveral parties. Customary land with the principle of communal ownership, the use and distribution of itsuse is subject to regulation according to customary law. In Pantai Cermin Village, Tapung Subdistrict,Kampar Regency, the ruler of the authorized ulayat land is someone who is a custom called Datuk Ruler ofUlayat Land Rights named Datuk Ajo Panji Alam who issues a letter on ulayat land, known as LandAcquisition Certificate hereinafter referred to as SKPL. SKPL is a basic letter issued by the Ruler of UlayatRights Land, Datuk Ajo Panji Alam, as proof of customary land / land acquisition for use rights notownership rights. However, in reality many fields of SKPL are used as property rights. SKPL as a basicletter which is proof of release from the ruler of the customary land rights is increased again to become aLand Ownership Certificate (SKT), Statement of Compensation (SKGR) to the Certificate of Ownership(SHM). The purpose of this essay is: First, to find out the position of SKPL issued by adat stakeholders onland ownership over communal land. Second, to know the mechanism for transferring the right to use intoownership rights over communal land.This type of research can be classified as sociological, because in this study the author immediatelyconducted research on the location or place under study in order to provide a complete and clear picture ofthe problem under study. This research was conducted in Pantai Cermin Village, Tapung District, KamparRegency, while the population and samples were all parties related to the problems examined in this study,data sources used primary data, secondary data, and tertiary data, data collection techniques in this studyby observation, interview, questionnaire, and literature study.From the results of the study two things can be concluded. First, the position of SKPL is as a basicletter issued by Datuk Ajo Panji Alam as proof of customary land / land acquisition for use rights notownership rights. Second, the transfer mechanism, which starts from the management of SKPL to the levelof SHM. As all the steps to the management are fulfilled, the rights granted by the ruler of the customaryland of Datuk Ajo Panji Alam automatically which starts from the right to use, not the right of ownership,will change into one's own full rights. Author's suggestion, First, communal land should be for nephewchildren or tribal members. Secondly, the village government and the Datuk Ruler of Ulayat Land Rightsshould pay more attention to and supervise communal land use.Keywords: Position - SKPL - Ulayat Land